Chronic motor performance following different traumatic brain injury severity—A systematic review - Corrigan, Frances; Wee, Ing Chee; Collins-Praino, Lyndsey E. (Frontiers in Neurology, 2023)
Introduction: Traumatic brain injury (TBI) is now known to be a chronic disease, causing ongoing neurodegeneration and linked to increased risk of neurodegenerative motor diseases, like Parkinson’s disease and amyotrophic lateral sclerosis. While the presentation of motor deficits acutely following traumatic brain injury is well documented, however, less is known about how these evolve in the long-term post-injury, or how the initial severity of injury affects these outcomes. The purpose of this review therefore was to examine objective assessment of chronic motor impairment across the spectrum of TBI in both preclinical and clinical models. Methods: PubMed, Embase, Scopus, and PsycINFO databases were searched with a search strategy containing key search terms for TBI and motor function. Original research articles reporting chronic motor outcomes with a clearly defined TBI severity (mild, repeated mild, moderate, moderate-severe, severe) in an adult population were included Results: 97 studies met the inclusion criteria, incorporating 62 preclinical and 35 clinical studies. Motor domains examined included neuroscore, gait, fine-motor, balance and locomotion for preclinical studies and neuroscore, fine-motor, posture and gait for clinical studies. There was little consensus among the papers presented, with extensive differences both in assessment methodology of the tests and parameters reported. In general, an effect of severity was seen, with more severe injury leading to persistent motor deficits, although subtle fine motor deficits were also seen clinically following repeated injury. Only six clinical papers investigated motor outcomes beyond 10 years post-injury and 2 preclinical studies to 18-24 months post-injury, and, as such, the interaction between a previous TBI and aging on motor performance is yet to be comprehensively examined. Conclusion: Further research is required to establish standardised motor assessment procedures to fully characterise chronic motor impairment across the spectrum of TBI with comprehensive outcomes and consistent protocols. Longitudinal studies investigating the same cohort over time are also key for understanding the interaction between TBI and aging. This is particularly critical, given the risk of neurodegenerative motor disease development following TBI.